Phyllotaxy and environmental factors influences on leaf trait dimensions in Fraxinus mandshurica: a multidimensional approach within temperate forests - Mingyue Jin; Mingyue Jin; Mingyue Jin; Yunfei Diao; Yunfei Diao; Yunlong Wang; Mingke Zhang; Tianyi Wang; Yajun Ren; Yajun Ren; Yajun Ren; Ming Zhong; et al. (Frontiers in Plant Science)
IntroductionLight and soil nutrients are strong drivers of leaf trait variation, but the relative importance in shaping intraspecific trait variation across leaf developmental gradients remains poorly assessed. Previous studies mostly focused on single traits, while fewer have employed multidimensional trait syndromes framework to explore how plants optimize resource use and maintain physiological homeostasis.MethodsWe measured leaf economic traits (e.g., specific leaf area, leaf nitrogen concentration) and stomatal traits (e.g., stomatal density, size) in leaflets at different phyllotactic positions of the compound-leaved species Fraxinus mandshurica in temperate forests of Northeast China, while assessing the effects of phyllotaxy and environmental factors (light, soil nutrients) on these traits.ResultsWe found that (1) specific leaf area and leaf nitrogen concentration significantly increase along the phyllotaxy gradient (from phyllotaxy 1 to 6), while leaf dry matter content, leaf thickness, and stomatal density significantly decrease. No significant variation in the dimensions of economic and stomatal traits was observed across the phyllotaxy gradient; (2) phyllotaxy modulates trait coordination, with decoupled economic and stomatal traits at phyllotaxy 1 but coupled relationships at phyllotaxy 2–6; (3) environmental factors had a greater impact on economic trait dimensions variation, whereas phyllotaxy was more important for stomatal trait dimensions.DiscussionOur study highlights the significance of trait dimensions in understanding plant functional strategies. We emphasize that the influence of environmental factors or phyllotaxy on trait variation is trait-specific, indicating distinct mechanisms for resource acquisition and water use. We recommend considering phyllotaxy when predicting plant responses to environmental changes.